A comparison of the values systems of Mexican and American Youth - Peck, Robert F. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
The present paper reports findings with two different instruments which are part of the nine-instrument battery used in a multi-faceted research known as the Cross Cultural Study of Values. One is the Values Hierarchy and the other, one of the three Respect Questionnaires. Parallel forms of the tests in English and in Spanish were administered to two samples of college students; the English version was administered at the University of Texas and the Spanish version at the Universidad Nacional Autónoma de México. Results from these instruments show highly significant differences in the value patterns of Mexican college students and American college students. The American pattern portrays life as a relatively secure place, economically, with emphasis on equalitarian friendliness and rather comfortable self-assurance. The Mexican pattern shows characteristics of a close knit highly emotionalized, reciprocal dependence and dutifulness, within a firmly authoritarian framework. There is substantial agreement within each culture on a common array of values. This might well be termed a "core-culture” pattern.